Electrodeposition and Characterization of SiOx Films Photoactive in Organic Solution. Issue 3 (1st January 2016) - Krywko-Cendrowska, A.; Marot, L.; Strawski, M.; Steiner, R.; Meyer, E.
Abstract : The photoactive silicon based films were potentiostatically deposited on Au electrodes from 0.5 M SiHCl3 dissolved in 0.1 M solution of tetrabutylammonium bromide (TBAB) in propylene carbonate (PC). The cyclic voltammetry measurements showed that the range of SiHCl3 reduction was between −2.4 and −2.9 V vs. Ag quasi reference electrode (Ag). Dependence of different ratio of silicon oxides (SiOx ) and hydrogen terminated silicon (Si:H) on the electrodeposition potential was characterized by Raman and X-ray Photoelectron Spectroscopies (XPS). The spectroscopic studies revealed that the concentration of SiHCl3 and the electrodeposition potential were the most significant parameters of the deposition process. The highest concentration of lowly oxidized SiOx was observed for the films obtained at −2.7 V. Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM) observations revealed dependence of the layers' morphology on the deposition potential value i.e. the most uniform films were obtained at −2.7 V, whereas at −2.5 and −2.85 V the deposits were of a granular and sponge-like morphology. Deposits obtained at −2.5 and −2.7 V have shown n-type photoactivity in 0.1 M solution of TBAB in PC and the registered photocurrent density was up to 24 μA × cm −2 .